OVERCOMING SOCIAL INCLUSION BARRIERS FOR PEOPLE WITH INTELLECTUAL DISABILITY - Zorzi, Simone; Strods, Gunars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The cultural changes that have taken place and the social sciences contributions that have been published over the last few decades have inaugurated a new vision of people with disabilities that upholds the values of rights, equality, participation, and social inclusion. Although these changes have been widely supported through the ratification of important international treaties (for example, the United Nations Convention on the Rights of Persons with Disabilities) and by scientific evidence, however, they are still struggling to penetrate into the wider social and cultural system, or to become common practice in services directed at people with disabilities. Social inclusion for people with disabilities, and in particular intellectual disabilities, remains, in fact, a difficult objective to achieve. Above all, cultural barriers are still a hindering factor in social inclusion processes. This paper is a commentary on the research carried out within the two-year European project ESEC (Extending Social Educators Competences).